Future trends in food science and foodomics: a perspective view by the editorial team of Exploration of foods and foodomics - Ibáñez, Elena (2024)
In this perspective article, several internationally recognized experts, members of the editorial team of this journal, discuss a selection of current hot topics identified in Food Science and Foodomics. The topics are comprised of the main areas of Food Science and Foodomics, namely, food safety, food authenticity, food processing, and food bioactivity. Logically, several of the discussed topics involve more than one of the mentioned main areas. Regarding food safety, the topics discussed are the use of analytical nanotechnology, nanometrology, nano-chromatography; the determination of organic contaminants based on MS and NMR; the impact of microplastics and nanoplastics on food or the contamination of foods with plant toxins. Regarding food authenticity, the paper discusses the role of MS, NMR, biosensors and the new trends in foodomics for food authentication. In terms of food processing, the work shows interesting perspectives on novel processing technologies, the effect of food processing on the gut microbiota or in the interaction among secondary metabolites and macromolecules; the development of active packaging, and the potential effects of introducing recycled plastics in food packaging; the new green extraction and encapsulation strategies of bioactive compounds from food by-products; and the anti-biofilm capacity of natural compounds/extracts/vegetal oils and essential oils. Food bioactivity and the relation between food and health includes the bioavailability and bioaccessibility of bioactive compounds; new trends and challenges in the interaction of nutraceuticals with biological systems; how food matrix impacts the bioaccessibility of nutrients and bioactive compounds; or the study of biodiversity, food and human health through one-health concept. We anticipate elaborations on these hot topics will promote further studies in Food Science and Foodomics.